Antitássomai in Hosea 1.6 (LXX): Its Label of “Lexical Error” Reconsidered - Kabergs, Valérie (The Bible translator, 2014)
This contribution re-evaluates ἀντιτασσόμενος ἀντιτάξομαι-אשׂא אשׂנ in LXX and MT Hos 1.6. While commentators have tried to clarify the link between the Greek and Hebrew readings by referring to a different Hebrew Vorlage, BHQ labels the reading as a “lexical error” for which the LXX translator should be held responsible. Neither of these explanations, however, accounts for the possibility that the LXX rendering could have been caused by the translator’s exegesis. This article characterizes the reading as a contextually appropriate translation and thereby acknowledges the exegetical work of the Greek translator.